The antineoplastic busulphan impairs peritubular and Leydig cells, and vitamin B-12 stimulates spermatogonia proliferation and prevents busulphan-induced germ cell death - Sasso-Cerri, Estela [UNESP]; Oliveira, Barbara [UNESP]; Santi, Fabiane de; Beltrame, Flavia L.; Caneguim, Breno H.; Cerri, Paulo S. [UNESP] (Elsevier B.V., 2017)
Busulphan (Bu), an alkylating agent used for bone marrow and spermatogonial stem cell transplantation (SSCT), impairs Sertoli (SC) cells, which are necessary for the spermatogonial stem cell (SSC) homing during transplantation. As Leydig (LC) and peritubular myoid (PMC) cells are essential for SC support and maintenance of spermatogonial niche, we evaluated the impact of Bu on the LC and PMC structural integrity. Vitamin B-12 (B-12) has demonstrated beneficial effects against drug-induced testicular changes; thus, we also examined whether this vitamin is able to stimulate spermatogonia mitotic activity and prevent Bu-induced germ cell death. Rats received 10 mg/kg of Bu in the 1st and 4th days, and daily B-12 supplementation during Bu treatment and for 6 days after the last injection of Bu (Bu-6d), totaling 10 days of treatment. Other animals received the same treatment as Bu-6d, and B12 supplementation (Bu + 7dB(12)) or saline (Bu + 7dS) for 7 more days, totaling 17 days of treatment. Serum testosterone levels were measured. In the historesin-embedded testis sections, the seminiferous tubule and epithelial areas were measured, and the number of spermatogonia and PMC was quantified. Actin and 17 beta-HSD6 immunofluorescence was detected, and the number of TUNEL-positive LC and germ cells was computed. In Bu-6d, PMC number reduced, and a weak actin immunoexpression and death in these cells was observed. The testosterone levels reduced, and the interstitial tissue showed a weak 17 beta-HSD6 immunoexpression and increased number of TUNEL-positive LC. In Bu + 7dB(12), the number of spermatogonia was higher than in Bu-6d and Bu + 7dS, and the number of TUNEL-positive germ cells was significantly lower than in Bu + 7dS. Bu exerts a harmful impact on PMC and LC, reducing the testosterone levels. Vitamin B-12 prevents significantly Bu-induced germ cell death and stimulates spermatogonia proliferation, being a useful strategy for the enrichment of SSC in vitro and an adjuvant therapy for spermatogenesis recovery in oncologic patients.
Keywords: Chemotherapy; Alkylating agent; Testosterone levels; Spermatogonia; Apoptosis; Vitamin